Assignment of the N-terminal domain of mouse cGAS - Aucharova, Hanna; Linser, Rasmus (Technische Universität Dortmund, 2025)
Cyclic GMP-AMP synthase (cGAS) is a DNA-sensing enzyme that is a member of the nucleotidyltransferase (NTase) family and functions as a DNA sensor. The protein is comprised of a catalytic NTase core domain and an unstructured hypervariable N-terminal domain (NTD) that was reported to increase protein activity by providing an additional DNA-binding surface. We report nearly complete 1H, 15N, and 13C backbone chemical-shift assignments of mouse cGAS NTD (residues 5-146), obtained with a set of 3D and 4D solution NMR experiments. Analysis of the chemical-shift values confirms that the NTD is intrinsically disordered. These resonance assignments can provide the basis for further studies such as activation by DNA and protein-protein interactions.
Biomolecular NMR assignments; 19(1)
Keywords: Cyclic GMP-AMP synthase; cGAS; Intrinsically disordered proteins; IDPs; NMR spectroscopy; 540